Race, wages, and assimilation among Cuban immigrants - Madeline Zavodny (Federal Reserve Bank of Atlanta, 2003)
This study uses data from the 1980 and 1990 Census and the 1994-2000 Current Population Survey to examine the determinants of earnings among male Cuban immigrants in the United States by race. Nonwhite Cuban immigrants earn about 15 percent less than whites, on average. Much of the racial wage gap is due to differences in educational attainment, age at migration, and years in the United States, but the gap remains at almost 4 percent after controlling for such factors. Nonwhite Cuban immigrants also have lower returns to education than whites. A comparison to white, non-Hispanic U.S. natives indicates that nonwhite Cubans not only earn less initially than white Cubans on arrival in the United States but also do not significantly close the racial earnings gap over time.
Keywords: 330; Immigrants; Employment (Economic theory); Discrimination in employment